2018
DOI: 10.33885/sf.2018.48.1232
|View full text |Cite
|
Sign up to set email alerts
|

Primer reporte de Mortierella elongata como patógeno del cultivo del aguacate en Michoacán, México

Abstract: Antecedentes: Las especies del género Mortierella prosperan usualmente como saprófitas en el suelo y materia orgánica de diversos ecosistemas forestales. Tradicionalmente, se han aislado de los sistemas radicales de diversas especies vegetales. Adicionalmente, investigaciones realizadas en suelo de cultivo de aguacate para lograr la purificación de Pythophthora. cinnamomi indican que Mortierella spp. son hongos contaminantes, sin mencionar su patogenicidad.Objetivo: Esta investigación tuvo como objetivo identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Mortierella spp. have been hypothesized to act as plant protective microbes, suppressing soil-borne pathogens through competition or enhanced plant nutrient uptake ( Miao et al, 2016 ); however, a recent study from Mexico confirmed Mortierella elongata as an avocado pathogen, which suggests that Mortierella species may act as opportunistic phytopathogens in root-rot affected orchards ( Hernández Pérez et al, 2018 ). Interestingly, isolate Mortierella sp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mortierella spp. have been hypothesized to act as plant protective microbes, suppressing soil-borne pathogens through competition or enhanced plant nutrient uptake ( Miao et al, 2016 ); however, a recent study from Mexico confirmed Mortierella elongata as an avocado pathogen, which suggests that Mortierella species may act as opportunistic phytopathogens in root-rot affected orchards ( Hernández Pérez et al, 2018 ). Interestingly, isolate Mortierella sp.…”
Section: Discussionmentioning
confidence: 99%
“…These isolates mostly belonged to the genus Fusarium , which confirms the findings by Carranza-Rojas et al (2015) who found several Fusarium species (Hypocreales), among which F. solani and F. sambucinum , to be associated with avocado root rot. Other fungal genera such as Lasiodiplodia (Botryosphaeriales), Scytalidium (Helotiales) and Mortierella (Mortierellales) have been previously reported as avocado pathogens in Peru, Spain, South Africa and Mexico ( Alama et al, 2006 ; Coertzen and Fourie, 2017 ; Hernández Pérez et al, 2018 ; Arjona-Girona et al, 2019 ). Sequencing of the fungal microbiome confirmed that Helotiales and Mortierellales were dominant taxa in the rhizosphere of root rot symptomatic trees, which suggests that these taxa could act as opportunistic fungal pathogens following root rot infection.…”
Section: Discussionmentioning
confidence: 99%
“…A common member of this genus, M. alpina, can induce several plant diseases, such as seedling necrosis of Pinus nigra [50] and seedling necrosis of the phloem of Araucaria araucana [51]. M. elongata has been found to cause diseases in avocado plants [52]. Furthermore, our study observed that M. alpina can severely infect the leaves and fruits of three other Rosaceae plants, including P. persica, P. bretschneideri, and P. salicina.…”
Section: Discussionmentioning
confidence: 52%
“…Este género se reportó por primera vez en São Paulo, SP, Brasil, en el 2020, en Bolivia en el año 2019, y en 2021 en Italia (Perini et al, 2021;Trierveiler-Pereira y Gugliotta, 2020;Maillard y Rocabado, 2019). Hernández (1974) realizó los primeros registros de este género en los estados de Guerrero e Hidalgo, los cuales cuentan con una biodiversidad fúngica muy extensa.…”
Section: Descripciónunclassified